The Influence of Parenting and Self-Control Influence toward Online Gaming among Adolescents: The Influence of Parenting and Self-Control Influence toward Online Gaming among Adolescents - Anika Fatima; Dwi Hastuti; Yulina Eva Riany (Journal of Family Sciences, 2020)
Online gaming is an action of playing the game with multiple player using internet connection. This study aims to analyze parent's emotional parenting practice and adolescent self-control on online gaming behavior among adolescents. The population in this research are vocational high-school students in Bekasi City. The school used in this research is chosen purposively that is State Vocational High-school 2 in Bekasi City. After 204 adolescents chosen, non-proportional random sampling was conducted to 60 respondents as sample between 16 until 18 years old who enrolled in vocational high school in Bekasi city. Data were collected by questionnaire with self-report technique. Most of the male and female adolescent emotional parenting practices are in a low category. Most male adolescent self-control are in the low category and females are in the middle category. Female adolescent self-control is higher than male adolescent. Most of the respondents are in the low category of online gaming. Male adolescents have higher rate of online gaming than female adolescent. There's a negative correlation between age, sex difference, negative and self-control with online gaming. There are direct influence of self-control and positive indirect effect of emotional parenting practice through self-control to online gaming.